Flexible non-combustible fabric as well as preparation method and application thereof

Through the independently developed non-combustible fibers and pretreatment liquid, combined with ring spinning and warp knitting technology, the problems of complex composite fiber blending process and poor spinningability of carbon fibers are solved, and high-performance flexible non-combustible fabrics are prepared with excellent combustion performance and mechanical properties, suitable for a variety of fire-proof applications.

CN119243395APending Publication Date: 2025-01-03SICHUAN JIUGAI INTELLIGENT EQUIPMENT CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411567900.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing composite fiber blending process is complex and the carbon fiber is poor, resulting in the flame retardant fabrics having a rough and hard feel, low strength, and easy carbonization. The elastic properties of flame retardant adhesives are poor, making it difficult to meet the market demand for flame retardant fabrics.

Method used

Using independently developed non-combustible fibers to make yarns by ring spinning and knitted with mixed fiber warp and wefts to form flexible non-combustible fabrics. A specific spinning process and pretreatment liquid is used to improve the fiber properties and strength of the fibers, including polyacrylonitrile spinning Preparation of silk liquid and gradient heating preoxidation treatment combined with modified multi-wall carbon nanotubes and surfactant pretreatment liquid to improve antistatic and mechanical properties.

Benefits of technology

The flexible non-combustible fabric prepared has high elongation of break, tensile strength, and extreme oxygen index. The carbonization temperature is as high as 640℃. Its performance is better than similar products on the market. It is suitable for various fire-proof products, and it is lightweight, easy to clean, and does not Characteristics of deformation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119243395A_ABST
    Figure CN119243395A_ABST
Patent Text Reader

Abstract

The invention discloses a flexible non-combustible fabric and a preparation method thereof, and the preparation method comprises the following steps: (1) adding non-combustible fiber and mixed fiber raw materials into a pretreatment mixed solution according to parts by weight, filling nitrogen, and maintaining for 30-40 minutes in a hydrothermal environment at 70-90 DEG C; (2) carrying out blowing, cotton carding, drawing, roving, spinning, doubling and twisting on the pretreated fiber raw material to prepare yarns, and weaving the yarns to obtain a basic fabric; and (3) shaping: desizing the basic fabric in water containing a cleaning agent at the temperature of 95 DEG C for 40-70 minutes, washing off slurry on the surface of the fabric, and then drying on a shaping machine at the temperature of 90-115 DEG C to obtain the flexible non-combustible fabric. The flexible non-combustible fabric prepared by adopting the method has the remarkable characteristics of non-combustion, non-shrinkage and non-dripping, also has the advantages of light weight and high strength, and is used for firefighter uniform, fire blanket, special protective clothing, seat cover cushions of transportation means, curtains and tablecloth in public places and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of new materials, and in particular relates to a flexible non-combustible fabric and a preparation method and application thereof. Background Art

[0002] Textiles are necessities in people's daily life. With the improvement of people's living standards, people's requirements for textile fabrics are getting higher and higher. Textiles with special functions are becoming more and more popular, such as magnetic shielding and other functions. Among them, flame retardant function is the most demanded functional product in the market. Flame retardant, heat insulation, anti-static, according to data records, fires caused by textiles catching fire or textiles with poor flame retardancy account for about 20% of fire accidents in my country over the years; therefore, flame retardant fabrics have become a textile product in urgent demand in the current market. At present, most of the common flame retardant fabrics on the market are fiber fabrics such as polyester fiber or aramid fabric, which have certain flame retardancy, but generally have defects such as rough feel, low strength, shrinkage when exposed to fire, and carbonization at 370℃, so they still cannot meet the existing market demand for flame retardant fabrics.

[0003] Non-flammable fabrics are known as industrial wool. They are resistant to high temperatures, do not burn, do not shrink, do not drip, are resistant to corrosion, and are resistant to cutting. They can be widely used in firefighting, metallurgy, petroleum, electrical welding, steel mills and other industries. They can be used in the development of firefighting suits, fire blankets, special industry work clothes, curtains, bedding, military supplies, seat covers and other products. In the currently disclosed prior art, most of the non-combustible fabrics are flame-retardant fabrics obtained by blending composite fibers. For example, patent publication number CN105105380B discloses an elastic flame-retardant composite fabric and its preparation method and application. Flame-retardant polyester fabric, flame-retardant heat-insulating elastic polyester coil, and flame-retardant non-woven fabric are bonded by flame-retardant adhesives. However, the elasticity of the flame-retardant adhesive is poor. Once the fabric is pulled, the flame-retardant adhesive will crack or break and have gaps, which easily leads to a reduction in the fire-retardant effect. Although blended flame-retardant fabrics can improve the flame retardancy of fabrics, since they are blended with multiple fibers, they need to go through spinning, weaving and dyeing and finishing processes. These processes also greatly affect or even determine the flame retardancy, mechanical and wearing properties of the final fabric. For example, flame-retardant carbon fiber has high modulus, high strength, strong rigidity, poor cohesion between fibers, and poor spinnability, so the spinning difficulty is very high. Summary of the invention

[0004] In view of the problems existing in the prior art, the present invention aims to provide a flexible non-combustible fabric and a preparation method thereof, which solves the defects of the existing complex composite fiber blending process and poor spinnability of carbon fiber. The present invention selects independently developed non-combustible fibers and adopts a specific spinning process to prepare non-combustible fabrics, which have the functions of non-combustion, non-melting, corrosion resistance, cut resistance, wear resistance, easy cleaning, and no invariance.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A flexible non-combustible fabric, which is made of non-combustible fiber and mixed fiber through ring spinning into yarn, and the yarn is knitted through warp and weft; the weight part of the non-combustible fiber is 70-100 parts, and the weight part of the mixed fiber is 0-30 parts.

[0007] The present invention uses independently developed non-combustible fibers with an elongation at break higher than 24%, high tensile strength, excellent fiber properties, and a limiting oxygen index higher than 45%, and can be used to be processed into non-combustible fabrics. The pre-oxidized silk fibers prepared by the present invention can be used to spin high-count yarns of 32-40 counts, while traditional pre-oxidized silk fibers can only spin yarns of 21 counts.

[0008] Preferably, the non-combustible fiber is prepared by the following method:

[0009] (1) acrylonitrile, N-vinyl amide monomer, isobutyl itaconate and an initiator are mixed and subjected to polymerization reaction, and then filtered, de-monomerized and defoamed to obtain a polyacrylonitrile spinning solution;

[0010] (2) The polyacrylonitrile spinning solution is subjected to spinneret treatment to obtain polyacrylonitrile precursor, the polyacrylonitrile precursor is immersed in a cobalt sulfate solution with a mass concentration of 5% for 5-10 minutes, and then immersed in a pretreatment solution composed of a mixed aqueous solution of succinic acid and sodium lauroyl methyl taurate for 10-15 minutes, and the soaked precursor is pre-oxidized by gradient heating to obtain non-combustible fiber.

[0011] Preferably, the mixed fiber includes one or more mixtures of methyl methacrylate, aramid, metal fiber, and synthetic fiber. In addition to the above fibers, the non-combustible fiber of the present invention can also be compounded with other fiber materials (such as ceramic fiber). According to different needs, other fibers can be mixed in the non-combustible fiber to give the fabric multiple functions, such as improving the conductivity, shielding performance, elastic modulus, insulation, chemical corrosion resistance, thermal insulation performance, etc. of the fabric.

[0012] The present invention also provides a method for preparing a flexible non-combustible fabric, comprising the following steps:

[0013] (1) Pretreatment: adding non-combustible fiber and mixed fiber raw materials into a pretreatment liquid according to weight, charging with nitrogen, and curing in a hydrothermal environment at 70-90° C. for 30-40 min; wherein the pretreatment liquid comprises polyether phosphate, modified multi-walled carbon nanotubes, a surfactant, and an ethanol aqueous solution;

[0014] (2) Spinning: The fiber raw material pretreated in step (1) is subjected to the processes of cleaning, combing, drawing, roving, spinning, winding and twisting to form yarn;

[0015] (3) Weaving: Weaving the yarn prepared in step (2) to obtain a base fabric;

[0016] (4) Shaping: Desizing the base fabric woven in step (3) in water containing a detergent at a temperature of 95° C. for 40-70 minutes to remove the slurry on the surface of the fabric, and then drying it on a setting machine at 90-115° C. to obtain the flexible non-flammable fabric.

[0017] Preferably, the pretreatment liquid in step (1) is composed of the following raw materials in parts by weight: 10-20 parts of polyether phosphate, 2-10 parts of modified multi-walled carbon nanotubes, 1-5 parts of surfactant, and 65-87 parts of ethanol aqueous solution.

[0018] Preferably, the modified multi-walled carbon nanotubes are obtained by oxidizing the multi-walled carbon nanotubes and then subjecting them to an acyl chlorination reaction; the acyl chlorination reaction is to react the oxidized multi-walled carbon nanotubes with thionyl chloride, so that the modified multi-walled carbon nanotubes have a larger specific surface area, and the acyl chlorination treatment can enhance the bonding ability of the carbon nanotubes with other materials.

[0019] Preferably, the surfactant is a cationic surfactant or a nonionic surfactant, the cationic surfactant includes one or more mixtures of dodecyltrimethylammonium chloride, hexadecyltrimethylammonium bromide, and octadecyldimethylbenzylammonium chloride; the nonionic surfactant includes one or a mixture of polyoxyethylene alkylamine and tetrabromobisphenol.

[0020] Preferably, the mass percentage of ethanol in the ethanol aqueous solution is 50%.

[0021] Preferably, the pretreatment liquid is prepared by the following method: 10-20 parts by weight of polyether phosphate, 2-10 parts by weight of modified multi-walled carbon nanotubes, and 1-5 parts by weight of a surfactant are mixed and heated to 50-80°C, and then 65-87 parts by weight of an ethanol aqueous solution are added, stirred and emulsified for 0.5-1 hour, and then cooled to room temperature and taken out to obtain the pretreatment liquid.

[0022] Preferably, the cleaning agent in step (4) is a soap detergent.

[0023] The present invention also provides the application of the non-combustible fabric prepared by the method, which is used for fire-fighting clothing, fire blankets, special protective clothing, seat covers of transportation vehicles, curtains and tablecloths in public places.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] (1) The present invention adopts independently developed non-combustible fibers, which have high tensile strength, elongation greater than 24%, and limiting oxygen index greater than 45%, and have excellent non-combustibility and fiber spinnability. The non-combustible fibers are pretreated with a pretreatment liquid independently developed to reduce static electricity generation between fibers, so that the fibers have a stronger cohesion, and fabrics with higher strength, flexibility and high breaking strength are woven through improved spinning and weaving processes. The non-combustible fibers prepared by the present invention can be used to spin 30-40 count high-count fabrics, while most of the same type of fibers on the market can only spin 21 count yarns.

[0026] (2) The non-combustible fiber pretreatment liquid independently developed by the present invention is composed of polyether phosphate, modified multi-walled carbon nanotubes, surfactant, and ethanol aqueous solution. The polyether phosphate with antistatic effect is compounded with the modified multi-walled carbon nanotubes, which can improve the antistatic performance and the strength of the fiber at the same time. The compatibility of the compound system is improved by adding surfactants, so that the polyether phosphate with antistatic performance and the multi-walled carbon nanotubes can interact with each other, thereby improving the antistatic and mechanical properties of the pretreatment liquid to enhance the non-combustible fiber.

[0027] (3) The flexible non-combustible fabric prepared by the method of the present invention has the remarkable characteristics of non-combustion, non-melting and non-drip, the carbonization temperature is as high as 640°C, the maximum temperature resistance is as high as 1100°C, it can be used for a long time in an air environment of 500°C, and can last for about 3 minutes at a high temperature of 800°C. Its performance is significantly higher than similar flame-retardant fabrics currently on the market; the limiting oxygen index is between 42-50%, which is 14-22% higher than similar flame-retardant products currently available, and can be widely used in various fire-proof products and places.

[0028] (4) The flexible non-flammable fabric prepared by the method of the present invention also has the advantages of light weight and high breaking strength. After blending with other fibers, its warp strength can reach 1100N, weft strength 1000N, and tear strength greater than 100N. It also has good air permeability, is easy to clean, and does not deform, and can be used to make clothing for special industries. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0030] Figure 1 This is a physical picture of the non-combustible fabric prepared in Example 3 of the present invention;

[0031] Figure 2This is a burn-through resistance test effect diagram of the non-combustible fabric prepared in Example 3 of the present invention;

[0032] Figure 3 This is a burn-through test result of commercially available non-flammable fabrics;

[0033] Figure 4 This is an experimental diagram of the combustion process of a flame retardant bag prepared using the non-combustible fabric of Example 3 of the present invention. DETAILED DESCRIPTION

[0034] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. In the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other.

[0035] A flexible non-combustible fabric comprises at least the following raw materials in parts by weight: 70-100 parts of non-combustible fibers and 0-30 parts of mixed fibers.

[0036] As a preferred embodiment, the flexible non-combustible fabric of the present invention comprises the following raw materials in parts by weight: 70-90 parts of non-combustible fibers and 10-30 parts of mixed fibers.

[0037] As another preferred embodiment, the flexible non-combustible fabric of the present invention comprises the following raw materials in parts by weight: 70-90 parts of non-combustible fiber and 10-30 parts of aramid fiber.

[0038] As another preferred embodiment, the flexible non-combustible fabric of the present invention comprises the following raw materials in parts by weight: 70-90 parts of non-combustible fiber and 10-30 parts of methyl methacrylate fiber.

[0039] As another preferred embodiment, the flexible non-combustible fabric of the present invention comprises the following raw materials in parts by weight: 70-90 parts of non-combustible fibers and 10-30 parts of metal fibers.

[0040] As another preferred embodiment, the flexible non-combustible fabric of the present invention comprises the following raw materials in parts by weight: 70-90 parts of non-combustible fibers and 10-30 parts of synthetic fibers.

[0041] As another preferred embodiment, the flexible non-combustible fabric of the present invention comprises the following raw materials in parts by weight: 70-90 parts of non-combustible fiber, 5-15 parts of methyl methacrylate fiber, and 5-15 parts of aramid fiber.

[0042] As another preferred embodiment, the flexible non-combustible fabric of the present invention comprises the following raw materials in parts by weight: 70-90 parts of non-combustible fiber, 5-15 parts of aramid fiber, and 5-15 parts of metal fiber.

[0043] As another preferred embodiment, the flexible non-combustible fabric of the present invention comprises the following raw materials in parts by weight: 70-90 parts of non-combustible fiber, 5-15 parts of aramid fiber, and 5-15 parts of synthetic fiber.

[0044] As another preferred embodiment, the flexible non-combustible fabric of the present invention comprises the following raw materials in parts by weight: 70-90 parts of non-combustible fibers, 5-15 parts of metal fibers, and 5-15 parts of synthetic fibers.

[0045] As another preferred embodiment, the flexible non-combustible fabric of the present invention comprises the following raw materials in parts by weight: 70-90 parts of non-combustible fiber, 3-10 parts of methyl methacrylate fiber, 4-10 parts of aramid fiber, and 3-10 parts of synthetic fiber.

[0046] As another preferred embodiment, the flexible non-combustible fabric of the present invention comprises the following raw materials in parts by weight: 70-90 parts of non-combustible fiber, 4-10 parts of aramid fiber, 3-10 parts of metal fiber, and 3-10 parts of synthetic fiber.

[0047] As another preferred embodiment, the flexible non-combustible fabric of the present invention comprises the following raw materials in parts by weight: 70-90 parts of non-combustible fiber, 3-10 parts of methyl methacrylate fiber, 4-10 parts of aramid fiber, and 3-10 parts of metal fiber.

[0048] As another preferred embodiment, the flexible non-combustible fabric of the present invention comprises the following raw materials in parts by weight: 70-90 parts of non-combustible fiber, 4-10 parts of methyl methacrylate fiber, 3-10 parts of metal fiber, and 3-10 parts of synthetic fiber.

[0049] It should be noted that the aramid fiber includes but is not limited to aramid 1414 and aramid 1313. Aramid 1313 is selected in the embodiment of the present invention.

[0050] It should be noted that the metal fiber includes but is not limited to stainless steel fiber, copper fiber, and alloy fiber. The metal fiber selected in the embodiment of the present invention is 316L stainless steel fiber.

[0051] It should be noted that the synthetic fiber includes but is not limited to at least one of polyester fiber, polyolefin fiber, polyurethane elastic fiber, polyoxymethylene fiber, and phenolic fiber. The synthetic fiber selected in the embodiment of the present invention is polyurethane elastic fiber.

[0052] The method for preparing the non-combustible fiber comprises the following steps:

[0053] (1) acrylonitrile, N-vinyl amide monomer, isobutyl itaconate and an initiator are mixed and subjected to polymerization reaction, and then filtered, de-monomerized and defoamed to obtain a polyacrylonitrile spinning solution;

[0054] (2) The polyacrylonitrile spinning solution is subjected to spinneret treatment to obtain polyacrylonitrile precursor, the polyacrylonitrile precursor is immersed in a cobalt sulfate solution with a mass concentration of 5% for 5-10 minutes, and then immersed in a pretreatment solution composed of a mixed aqueous solution of succinic acid and sodium lauroyl methyl taurate for 10-15 minutes, and the soaked precursor is pre-oxidized by gradient heating to obtain non-combustible fiber.

[0055] In step (1) of the method for preparing the non-combustible fiber, the N-vinyl amide monomer is N-vinylacetamide or N,N'-vinylbisacrylamide or N-ethylacrylamide.

[0056] As a method for preparing non-combustible fiber, the method comprises the following steps:

[0057] (1) preparing polyacrylonitrile spinning solution: dissolving 98 parts of acrylonitrile, 0.6 parts of N-vinylacetamide and 0.2 parts of isobutyl itaconate in 380 parts of N,N-dimethylformamide, then adding 20 parts of benzoyl peroxide-N,N-diethylaniline and heating the mixture until the temperature reaches 60°C, and then continuously adding the remaining 1.0 parts of N-vinylacetamide and 0.2 parts of isobutyl itaconate, and the addition is completed within 3 hours, reacting at 65°C for 2 hours, and then heating the mixture to a second stage of 75°C at a heating rate of 0.1°C / min and reacting for 12 hours to obtain a polyacrylonitrile polymer, and then filtering and removing the monomers to obtain a polyacrylonitrile spinning solution;

[0058] (2) Preparation of polyacrylonitrile precursor:

[0059] a. The polyacrylonitrile spinning solution is extruded from the spinneret through negative pressure degassing, and the polyacrylonitrile primary fiber is obtained by wet spinning, the spinneret aperture is 0.07-0.08mm, and the coagulation bath is selected from a 60% by mass DMSO aqueous solution at a temperature of 55°C;

[0060] b. The solvent is removed from the deionized water obtained in step (1); after deionized water, two-stage hot water drawing is performed, the first stage hot water temperature is 60 ℃, and the drawing ratio is 1.4 times; the second stage hot water temperature is 90 ℃, and the drawing ratio is 1.6 times;

[0061] c. After hot water drawing, the washed silk is air-dried and then oiled in a silicone oil aqueous solution, with the mass fraction of the oil being 0.65%;

[0062] d. The oiled fiber was dried and densified at 152°C, and then stretched with high-pressure steam at a steam pressure of 0.45 MPa and a stretching ratio of 4 times to obtain the polyacrylonitrile precursor;

[0063] (3) soaking the polyacrylonitrile precursor in a cobalt sulfate solution with a mass concentration of 5% for 8 minutes, and then soaking it in a pretreatment solution for 12 minutes, wherein the mass concentration of succinic acid in the pretreatment solution is 0.3%, and the mass concentration of sodium lauroyl methyl taurate is 1.3%;

[0064] (4) Preparation of non-combustible fiber: The above-mentioned polyacrylonitrile precursor was placed in an oxidation furnace, and the temperature in the furnace was raised from 25°C to 200°C in an air atmosphere at a heating rate of 3°C / min, and kept at this temperature for 10 min. The temperature was then raised to 220°C at a heating rate of 2°C / min, and kept at this temperature for 10 min. Thereafter, the temperature was raised to 240°C at a heating rate of 1°C / min, and kept at this temperature for 30 min. The non-combustible fiber 1# was obtained by naturally cooling to room temperature.

[0065] As a method for preparing non-combustible fiber, the method comprises the following steps:

[0066] (1) preparing polyacrylonitrile spinning solution: dissolving 98 parts of acrylonitrile, 0.6 parts of N,N'-vinylbisacrylamide and 0.2 parts of isobutyl itaconate in 380 parts of N,N-dimethylformamide, then adding 20 parts of benzoyl peroxide-N,N-diethylaniline and heating the mixture until the temperature reaches 60°C, and then continuously adding the remaining 1.0 parts of N-vinylacetamide and 0.2 parts of isobutyl itaconate within 3 hours, reacting at 65°C for 2 hours, and then heating the mixture at a heating rate of 0.1°C / min to a second stage of 75°C for 12 hours to obtain a polyacrylonitrile polymer, and then filtering and removing the monomers to obtain a polyacrylonitrile spinning solution;

[0067] (2) Preparation of polyacrylonitrile precursor:

[0068] a. The polyacrylonitrile spinning solution is extruded from the spinneret through negative pressure degassing, and the polyacrylonitrile primary fiber is obtained by wet spinning, the spinneret aperture is 0.07-0.08mm, and the coagulation bath is selected from a 60% by mass DMSO aqueous solution at a temperature of 55°C;

[0069] b. The solvent is removed from the deionized water obtained in step (1); after deionized water, two-stage hot water drawing is performed, the first stage hot water temperature is 60 ℃, and the drawing ratio is 1.4 times; the second stage hot water temperature is 90 ℃, and the drawing ratio is 1.6 times;

[0070] c. After hot water drawing, the washed silk is air-dried and then oiled in a silicone oil aqueous solution, with the mass fraction of the oil being 0.65%;

[0071] d. The oiled fiber was dried and densified at 152°C, and then stretched with high-pressure steam at a steam pressure of 0.45 MPa and a stretching ratio of 4 times to obtain the polyacrylonitrile precursor;

[0072] (3) soaking the polyacrylonitrile precursor in a cobalt sulfate solution with a mass concentration of 5% for 8 minutes, and then soaking it in a pretreatment solution for 12 minutes, wherein the mass concentration of succinic acid in the pretreatment solution is 0.3%, and the mass concentration of sodium lauroyl methyl taurate is 1.3%;

[0073] (4) Preparation of non-combustible fiber: The above-mentioned polyacrylonitrile precursor was placed in an oxidation furnace, and the temperature in the furnace was raised from 25°C to 200°C in an air atmosphere at a heating rate of 3°C / min, and kept warm for 10 min. The temperature was then raised to 220°C at a heating rate of 2°C / min, and kept warm for 10 min. Thereafter, the temperature was raised to 240°C at a heating rate of 1°C / min, and kept warm for 30 min. The non-combustible fiber 2# was obtained by naturally cooling to room temperature.

[0074] As a method for preparing non-combustible fiber, the method comprises the following steps:

[0075] (1) preparing polyacrylonitrile spinning solution: dissolving 98 parts of acrylonitrile, 0.6 parts of N-ethylacrylamide and 0.2 parts of isobutyl itaconate in 380 parts of N,N-dimethylformamide, then adding 20 parts of benzoyl peroxide-N,N-diethylaniline and heating the mixture until the temperature reaches 60°C, and then continuously adding the remaining 1.0 parts of N-vinylacetamide and 0.2 parts of isobutyl itaconate, and the addition is completed within 3 hours, reacting at 65°C for 2 hours, and then heating the mixture to a second stage of 75°C at a heating rate of 0.1°C / min and reacting for 12 hours to obtain a polyacrylonitrile polymer, and then filtering and removing the monomers to obtain a polyacrylonitrile spinning solution;

[0076] (2) Preparation of polyacrylonitrile precursor:

[0077] a. The polyacrylonitrile spinning solution is extruded from the spinneret through negative pressure degassing, and the polyacrylonitrile primary fiber is obtained by wet spinning, the spinneret aperture is 0.07-0.08mm, and the coagulation bath is selected from a 60% by mass DMSO aqueous solution at a temperature of 55°C;

[0078] b. The solvent is removed from the deionized water obtained in step (1); after deionized water, two-stage hot water drawing is performed, the first stage hot water temperature is 60 ℃, and the drawing ratio is 1.4 times; the second stage hot water temperature is 90 ℃, and the drawing ratio is 1.6 times;

[0079] c. After hot water drawing, the washed silk is air-dried and then oiled in a silicone oil aqueous solution, with the mass fraction of the oil being 0.65%;

[0080] d. The oiled fiber was dried and densified at 152°C, and then stretched with high-pressure steam at a steam pressure of 0.45 MPa and a stretching ratio of 4 times to obtain the polyacrylonitrile precursor;

[0081] (3) soaking the polyacrylonitrile precursor in a cobalt sulfate solution with a mass concentration of 5% for 8 minutes, and then soaking it in a pretreatment solution for 12 minutes, wherein the mass concentration of succinic acid in the pretreatment solution is 0.3%, and the mass concentration of sodium lauroyl methyl taurate is 1.3%;

[0082] (4) Preparation of non-combustible fiber: The above-mentioned polyacrylonitrile precursor was placed in an oxidation furnace, and the temperature in the furnace was raised from 25°C to 200°C in an air atmosphere at a heating rate of 3°C / min, and kept at this temperature for 10 min. The temperature was then raised to 220°C at a heating rate of 2°C / min, and kept at this temperature for 10 min. Thereafter, the temperature was raised to 240°C at a heating rate of 1°C / min, and kept at this temperature for 30 min. The non-combustible fiber 3# was obtained by naturally cooling to room temperature.

[0083] The preparation method of the flexible non-combustible fabric of the present invention comprises the following steps:

[0084] (1) Pretreatment: adding non-combustible fiber and mixed fiber raw materials into a pretreatment liquid according to weight, charging with nitrogen, and curing in a hydrothermal environment at 70-90° C. for 30-40 min; wherein the pretreatment liquid comprises polyether phosphate, modified multi-walled carbon nanotubes, a surfactant, and an ethanol aqueous solution;

[0085] (2) Spinning: The fiber raw material pretreated in step (1) is subjected to the processes of cleaning, combing, drawing, roving, spinning, winding and twisting to form yarn;

[0086] (3) Weaving: Weaving the yarn prepared in step (2) to obtain a base fabric;

[0087] (4) Shaping: Desizing the base fabric woven in step (3) in water containing a detergent at a temperature of 95° C. for 40-70 minutes to remove the slurry on the surface of the fabric, and then drying it on a setting machine at 90-115° C. to obtain the flexible non-flammable fabric.

[0088] It should be noted that the modified multi-walled carbon nanotubes are obtained by oxidizing the multi-walled carbon nanotubes and then reacting them with thionyl chloride to obtain the modified multi-walled carbon nanotubes.

[0089] It should be noted that the surfactant is a cationic surfactant or a nonionic surfactant. The cationic surfactant includes one or more mixtures of dodecyltrimethylammonium chloride, hexadecyltrimethylammonium bromide, and octadecyldimethylbenzylammonium chloride; the nonionic surfactant includes one or a mixture of two of polyoxyethylene alkylamine and tetrabromobisphenol.

[0090] It should be noted that the specific process of spinning in step (2) is as follows:

[0091] 1) Cleaning: The pretreated fiber raw materials are manually arranged and put into the grabbing machine. The grabbing machine speed is 960r / min, the beater speed is 800r / min, the fan speed is 950r / min, the dry weight of the cotton roll is 320g / m, and the length of the cotton roll is 27m;

[0092] 2) Carding: Carding is produced on a carding machine. The speed of the carding roll is 300r / min, and the carding sliver speed is 100-140m / min. The fiber sliver obtained after carding has strong parallelism and mixing uniformity.

[0093] 3) Drawing: Two or more fiber slivers obtained by combing cotton are drawn together in two passes, and the bell mouth is 3.3mm; the fiber slivers are drawn together on a drawing frame, through a guide hook, a guide frame and a concave-convex roller, to obtain a first fiber drawing frame; wherein the first drawing frame has a sliver delivery speed of 250-450m / min, a roller spacing of 9*17mm, and a back-zone drafting of 1.7 times; two or more fiber slivers are drawn together on a second drawing frame, through a guide hook, a guide frame and a concave-convex roller, to obtain a second fiber drawing frame; wherein the second drawing frame has a sliver delivery speed of 250-450m / min, a roller spacing of 15*20mm, and a back-zone drafting of 1.6 times;

[0094] 4) Roving: The fiber prepared above is placed on a roving frame, and is stretched and twisted by a guide frame and a roller in a drafting zone to obtain roving; the spindle speed is 750-900 r / min, the twist is 350 twists / m, the roller gauge is 25*33 mm, the back zone drafting is 1.26 times, and the jaw gauge is 6.5 mm;

[0095] 5) Spinning: Then put the roving on the spinning frame, pass through the yarn drying rod, bell mouth, drafting roller and yarn guide hook, and stretch and twist it into a cop yarn; in the spinning frame, the spindle speed is 1200-1600m / min, the twist is 950 twists / m, the total drafting multiple is 30.2 times, and the back zone drafting is 1.3 times;

[0096] 6) Doubling: The obtained fine tube yarn is passed through the winding machine to increase the package quantity, and the yarn quality is tested by the electronic yarn clearer, and the unqualified yarn is removed, and finally the single yarn is wound; two single yarns are wound into a doubling bobbin in parallel to ensure that the tension on both sides is consistent; on the premise of ensuring good bobbin formation, the yarn tension should be as small as possible to protect the elasticity and strength of the original yarn, and 30-40 doubling yarns are produced; the winding speed is 900-1300m / min, the tension value is 5-8, and the yarn delivery speed is 750-1250m / min;

[0097] 7) Twisting: Two parallel yarns are made into ply yarns with a twist of 1050 twists / m and a double twist yarn density of 18 tex. The ply yarns produced are the non-combustible fiber ring-spun yarns.

[0098] It should be noted that the cleaning agent is a soap detergent.

[0099] Example 1

[0100] A method for preparing a flexible non-combustible fabric comprises the following steps:

[0101] (1) Pretreatment: 100 parts by weight of non-combustible fiber 1# is added to a pretreatment liquid, nitrogen is introduced, and the pretreatment liquid is cured in a hydrothermal environment at 70°C for 40 minutes; wherein the pretreatment liquid is prepared by the following method: 10 parts by weight of polyether phosphate, 2 parts by weight of modified multi-walled carbon nanotubes, and 1 part by weight of dodecyltrimethylammonium chloride are mixed and heated to 50°C, and then 87 parts by weight of ethanol aqueous solution are added, stirred and emulsified for 1 hour, and then cooled to room temperature and taken out to obtain the pretreatment liquid;

[0102] (2) Spinning: The fiber raw material pretreated in step (1) is subjected to the processes of cleaning, combing, drawing, roving, spinning, winding and twisting to form yarn;

[0103] (3) Weaving: Weaving the yarn prepared in step (2) to obtain a base fabric;

[0104] (4) Shaping: The base fabric woven in step (3) is desized in a soap detergent at a temperature of 95° C. for 40 minutes to remove the sizing on the surface of the fabric, and then dried on a shaping machine at 90° C. to obtain a flexible non-flammable fabric.

[0105] Example 2

[0106] A method for preparing a flexible non-combustible fabric comprises the following steps:

[0107] (1) Pretreatment: 100 parts by weight of non-combustible fiber 1# is added to a pretreatment liquid, nitrogen is introduced, and the pretreatment liquid is cured in a hydrothermal environment at 90°C for 30 minutes; wherein the pretreatment liquid is prepared by the following method: 20 parts by weight of polyether phosphate, 10 parts by weight of modified multi-walled carbon nanotubes, and 5 parts by weight of polyoxyethylene alkylamine are mixed and heated to 80°C, and then 65 parts by weight of ethanol aqueous solution are added, stirred and emulsified for 0.5 hours, and then cooled to room temperature and taken out to obtain the pretreatment liquid;

[0108] (2) Spinning: The fiber raw material pretreated in step (1) is subjected to the processes of cleaning, combing, drawing, roving, spinning, winding and twisting to form yarn;

[0109] (3) Weaving: Weaving the yarn prepared in step (2) to obtain a base fabric;

[0110] (4) Shaping: The base fabric woven in step (3) is desized in a soaping agent at a temperature of 95° C. for 70 minutes to remove the sizing on the surface of the fabric, and then dried on a setting machine at 115° C. to obtain a flexible non-flammable fabric.

[0111] Example 3

[0112] A method for preparing a flexible non-combustible fabric comprises the following steps:

[0113] (1) Pretreatment: 100 parts by weight of non-combustible fiber 1# is added to a pretreatment liquid, nitrogen is introduced, and the pretreatment liquid is cured in a hydrothermal environment at 80°C for 40 minutes; wherein the pretreatment liquid is prepared by the following method: 17 parts by weight of polyether phosphate, 7 parts by weight of modified multi-walled carbon nanotubes, and 4 parts by weight of hexadecyltrimethylammonium bromide are mixed and heated to 72°C, and then 72 parts by weight of ethanol aqueous solution are added, stirred and emulsified for 0.6 hours, and then cooled to room temperature and taken out to obtain the pretreatment liquid;

[0114] (2) Spinning: The fiber raw material pretreated in step (1) is subjected to the processes of cleaning, combing, drawing, roving, spinning, winding and twisting to form yarn;

[0115] (3) Weaving: Weaving the yarn prepared in step (2) to obtain a base fabric;

[0116] (4) Shaping: The base fabric woven in step (3) is desized in a soaping agent at a temperature of 95° C. for 65 minutes to remove the slurry on the surface of the fabric, and then dried on a setting machine at 110° C. to obtain a flexible non-flammable fabric.

[0117] Example 4

[0118] A method for preparing a flexible non-combustible fabric comprises the following steps:

[0119] Compared with Example 3, the non-combustible fiber 1# in Example 3 is replaced by non-combustible fiber 2#, and the remaining method steps are consistent with the method steps in Example 3 to prepare a flexible non-combustible fabric.

[0120] Example 5

[0121] A method for preparing a flexible non-combustible fabric comprises the following steps:

[0122] Compared with Example 3, the non-combustible fiber 1# in Example 3 is replaced by non-combustible fiber 3#, and the remaining method steps are consistent with the method steps in Example 3 to prepare a flexible non-combustible fabric.

[0123] Example 6

[0124] Compared with Example 3, 100 parts by weight of non-combustible fiber 1# in Example 3 are replaced by 80 parts by weight of non-combustible fiber 1# and 20 parts by weight of aramid 1313 fiber, and the remaining method steps are consistent with the method steps in Example 3 to prepare a flexible non-combustible fabric.

[0125] Example 7

[0126] Compared with Example 3, 100 parts by weight of non-combustible fiber 1# in Example 3 are replaced by 80 parts by weight of non-combustible fiber 1# and 20 parts by weight of methyl methacrylate fiber, and the remaining method steps are consistent with the method steps in Example 3 to prepare a flexible non-combustible fabric.

[0127] Example 8

[0128] Compared with Example 3, 100 parts by weight of non-combustible fiber 1# in Example 3 are replaced with 92 parts by weight of non-combustible fiber 1# and 8 parts by weight of 316L stainless steel fiber, and the remaining method steps are consistent with the method steps in Example 3 to prepare a flexible non-combustible fabric.

[0129] Example 9

[0130] Compared with Example 3, 100 parts by weight of non-combustible fiber 1# in Example 3 are replaced by 80 parts by weight of non-combustible fiber 1# and 20 parts by weight of polyurethane elastic fiber, and the remaining method steps are consistent with the method steps in Example 3 to prepare a flexible non-combustible fabric.

[0131] Example 10

[0132] Compared with Example 3, 100 parts by weight of non-combustible fiber 1# in Example 3 are replaced with 80 parts by weight of non-combustible fiber 1#, 10 parts by weight of aramid 1313 fiber, and 10 parts by weight of methyl methacrylate fiber, and the remaining method steps are consistent with the method steps in Example 3 to prepare a flexible non-combustible fabric.

[0133] Embodiment 11

[0134] Compared with Example 3, 100 parts by weight of non-combustible fiber 1# in Example 3 are replaced with 80 parts by weight of non-combustible fiber 1#, 6 parts by weight of methyl methacrylate fiber, 8 parts by weight of aramid 1313 fiber, and 6 parts by weight of 316L stainless steel fiber, and the remaining method steps are consistent with the method steps in Example 3 to prepare a flexible non-combustible fabric.

[0135] Comparative Example 1

[0136] Compared with Example 3, all 100 parts by weight of non-combustible fiber 1# in Example 3 are replaced by aramid 1313 fiber, and the remaining method steps are consistent with the method steps in Example 3 to prepare a non-combustible fabric.

[0137] Comparative Example 2

[0138] Compared with Example 6, 80 parts by weight of non-combustible fiber 1# in Example 6 are replaced with aramid 1313 fiber, 20 parts by weight of aramid 1313 fiber are replaced with non-combustible fiber 1#, and the remaining method steps are consistent with the method steps in Example 6 to prepare a non-combustible fabric.

[0139] Comparative Example 3

[0140] Compared with Example 7, 80 parts by weight of non-combustible fiber 1# in Example 7 is replaced with aramid 1313 fiber, and the remaining method steps are consistent with the method steps in Example 7 to prepare a non-combustible fabric.

[0141] Comparative Example 4

[0142] Compared with Example 10, 80 parts by weight of non-combustible fiber 1# in Example 10 are replaced with aramid fiber, 10 parts by weight of aramid 1313 fiber are replaced with non-combustible fiber 1#, and the remaining method steps are consistent with the method steps in Example 10 to prepare a non-combustible fabric.

[0143] Comparative Example 5

[0144] Compared with Example 11, 80 parts by weight of non-combustible fiber 1# in Example 11 are replaced with aramid fiber, 8 parts by weight of aramid 1313 fiber are replaced with non-combustible fiber 1#, and the remaining method steps are consistent with the method steps in Example 11 to prepare a non-combustible fabric.

[0145] Comparative Example 6

[0146] Compared with Example 3, in Comparative Example 11, in the pretreatment step, the pretreatment liquid is replaced with an ethanol aqueous solution, and the remaining method steps are consistent with the method steps in Example 3 to prepare a non-flammable fabric.

[0147] Comparative Example 7

[0148] Compared with Example 3, in Comparative Example 11, in the pretreatment step, 7 parts by weight of modified multi-walled carbon nanotubes in the pretreatment liquid are completely replaced with polyether phosphate, and the remaining method steps are consistent with the method steps in Example 3 to prepare a non-flammable fabric.

[0149] Comparative Example 8

[0150] Compared with Example 3, in Comparative Example 11, in the pretreatment step, 4 parts by weight of hexadecyltrimethylammonium bromide in the pretreatment liquid is replaced with modified multi-walled carbon nanotubes, and the remaining method steps are consistent with the method steps in Example 3 to prepare a non-flammable fabric.

[0151] Comparative Example 9

[0152] Compared with Example 3, in Comparative Example 11, in the pretreatment step, 17 parts by weight of polyether phosphate in the pretreatment liquid is replaced with modified multi-walled carbon nanotubes, and the remaining method steps are consistent with the method steps in Example 3 to prepare a non-flammable fabric.

[0153] Experimental analysis

[0154] Effect Example 1

[0155] The non-combustible fabrics prepared in Examples 1-17 and Comparative Examples 1-9 were subjected to performance tests to measure their combustion performance, antistatic performance, and strength. The test results are shown in Table 1.

[0156] The combustion performance test is carried out according to GB 8624-2012 "Classification of Combustion Performance of Building Materials and Products" to test the limiting oxygen index and vertical combustion performance (including afterburning time, smoldering time, damage length, and detection of burning drips);

[0157] Strength determination is based on GB / T 3923.1-2013 "Tensile properties of textile fabrics - Part 1: Determination of breaking strength and elongation at break" and is carried out by testing the breaking strength in the warp and weft directions respectively;

[0158] The antistatic performance is tested according to GB 12014-2019 "Appendix A on Static Electricity for Protective Clothing" to test the antistatic performance of fabrics.

[0159] It can be seen from Table 1 that the non-combustible fabric prepared by the present invention has excellent combustion performance, and the limiting oxygen index is higher than 45%, and has strong breaking strength and antistatic performance; it can be seen from the experimental data of comparative examples 1-5 that the non-combustible fabric prepared by the flame-retardant fiber independently developed by the present invention is superior to the performance of the commonly used flame-retardant fiber-aramid 1313 on the market in terms of both its combustion performance and breaking strength; at the same time, it can be seen from the experimental data of comparative examples 2-5 that the flame-retardant fiber independently developed by the present invention can be mixed with other fibers on the market to prepare non-combustible fabrics, and different fibers can be selected for blending according to the special needs of fabrics in different scenarios to further improve a certain specific performance of the fabric; it can be seen from the antistatic test data that the non-combustible fabric prepared by the present invention has a smaller surface resistance and better antistatic performance; it can be seen from comparative examples 6-9 that the antistatic performance of the prepared fabric is significantly enhanced by using the pretreatment independently developed by the present invention for fiber pretreatment, and the mutual cooperation of several components in the pretreatment of the present invention makes the antistatic effect better, and the lack of a certain component has a greater impact on the antistatic effect.

[0160] Table 1 Performance test results of non-flammable fabric samples

[0161]

[0162]

[0163] Effect Example 2

[0164] The inventors conducted a burn-through test on the non-combustible fabric prepared as above, respectively selecting the non-combustible fabric prepared in Example 3 of the present invention (experimental example) and purchasing a certain type of (aluminum oxide) non-combustible fabric on the market (comparative example) for the burn-through test; Figure 2-3The present inventor conducted a test experiment in the laboratory. From the experimental results, it can be seen that the non-combustible fabric prepared by the method of the present invention has strong resistance to burn-through. From the result comparison chart, it can be seen that the commercially available non-combustible fabric has a large area of ​​burn-through (see attached Figure 3 ), and the non-combustible fabric of the present invention only has small cracks after long-term burning (see attached Figure 2 ), further proving that the non-combustible fabric prepared by the present invention has a high non-combustible performance. At the same time, the inventor processed the non-combustible fabric prepared in Example 3 into a flame retardant bag, and tested the flame retardant effect of the flame retardant bag in the laboratory. The inventor filled the flame retardant bag with wood, then poured diesel into it for ignition and combustion, and observed the combustion of the flame retardant bag. Figure 4 It can be seen that the non-combustible fabric prepared by the present invention has the remarkable characteristics of non-combustion, non-melting and non-dropping. Through the combustion data test, it can be known that the carbonization temperature of the non-combustible fabric of the present invention is as high as 640°C, which has a significant non-combustible effect.

[0165] In summary, the present invention adopts independently developed flame-retardant fibers for spinning to prepare non-combustible fabrics, which have the remarkable characteristics of non-combustion, non-melting shrinkage and non-melting dripping, a carbonization temperature of up to 640°C, a maximum temperature resistance of up to 1100°C, a limiting oxygen index of between 42-50%, and can be used for a long time in an air environment of 500°C. Its performance is significantly higher than that of similar flame-retardant fabrics currently on the market; and it has the advantages of light weight and high breaking strength, with a warp strength of up to 1100N, a weft strength of 1000N, a tear strength greater than 100N, good air permeability, easy cleaning, and no deformation, and can be used for fire suits, fire blankets, special protective clothing, seat covers for transportation vehicles, curtains and tablecloths in public places, etc.

[0166] The above description is only a preferred embodiment of the present invention and is not intended to limit the protection scope of the present invention.

Claims

1. A flexible non-combustible fabric, characterized in that: The fabric is made of yarns made from non-combustible fibers and mixed fibers through ring spinning, and the yarns are knitted through warp and weft; the weight portion of the non-combustible fibers is 70-100 parts, and the weight portion of the mixed fibers is 0-30 parts.

2. The flexible non-combustible fabric according to claim 1, characterized in that: The non-combustible fiber is prepared by the following method: (1) acrylonitrile, N-vinyl amide monomer, isobutyl itaconate and an initiator are mixed and subjected to polymerization reaction, and then filtered, de-monomerized and defoamed to obtain a polyacrylonitrile spinning solution; (2) The polyacrylonitrile spinning solution is subjected to spinneret treatment to obtain polyacrylonitrile precursor, the polyacrylonitrile precursor is immersed in a cobalt sulfate solution with a mass concentration of 5% for 5-10 minutes, and then immersed in a pretreatment solution composed of a mixed aqueous solution of succinic acid and sodium lauroyl methyl taurate for 10-15 minutes, and the soaked precursor is pre-oxidized by gradient heating to obtain non-combustible fiber.

3. The flexible non-combustible fabric according to claim 1, characterized in that: The mixed fiber includes one or more mixtures of methyl methacrylate fiber, aramid fiber, metal fiber and synthetic fiber.

4. A method for preparing the flexible non-combustible fabric according to any one of claims 1 to 3, characterized in that: The steps include: (1) Pretreatment: adding non-combustible fiber and mixed fiber raw materials into a pretreatment mixed solution according to weight, charging with nitrogen, and curing in a hydrothermal solution at 70-90° C. for 30-40 min; wherein the pretreatment solution comprises polyether phosphate, modified multi-walled carbon nanotubes, a surfactant, and an ethanol aqueous solution; (2) Spinning: The fiber raw material pretreated in step (1) is subjected to the processes of cleaning, combing, drawing, roving, spinning, winding and twisting to produce yarn; (3) Weaving: Weaving the yarn prepared in step (2) to obtain a base fabric; (4) Shaping: Desizing the base fabric woven in step (3) in water containing a detergent at a temperature of 95° C. for 40-70 minutes to remove the slurry on the surface of the fabric, and then drying it on a setting machine at 90-115° C. to obtain the flexible non-flammable fabric.

5. The method for preparing the flexible non-combustible fabric according to claim 4, characterized in that: The pretreatment liquid in step (1) is composed of the following raw materials in parts by weight: 10-20 parts of polyether phosphate, 2-10 parts of modified multi-walled carbon nanotubes, 1-5 parts of surfactant, and 65-87 parts of ethanol aqueous solution.

6. The method for preparing the flexible non-combustible fabric according to claim 5, characterized in that: The modified multi-walled carbon nanotubes are obtained by oxidizing the multi-walled carbon nanotubes and then subjecting them to an acyl chloride reaction.

7. The method for preparing the flexible non-combustible fabric according to claim 5, characterized in that: The surfactant is a cationic surfactant or a nonionic surfactant. The cationic surfactant includes one or more mixtures of dodecyltrimethylammonium chloride, hexadecyltrimethylammonium bromide, and octadecyldimethylbenzylammonium chloride; the nonionic surfactant includes one or a mixture of polyoxyethylene alkylamine and tetrabromobisphenol.

8. The method for preparing the flexible non-combustible fabric according to claim 4, characterized in that: The mass percentage of ethanol in the ethanol aqueous solution is 50%.

9. The method for preparing the flexible non-combustible fabric according to claim 4, characterized in that: The cleaning agent in step (4) is a soaping agent.

10. An application of the flexible non-combustible fabric prepared according to claims 1-9, characterized in that: The fabric is used for fire-fighting clothing, fire blankets, special protective clothing, seat covers of transportation vehicles, curtains and tablecloths in public places.

Citation Information

Patent Citations

  • Polyacrylonitrile suspension with high solid content and low viscosity, preparation method and application thereof, and preparation method of polyacrylonitrile-based carbon fiber

    CN113072658A

  • Flame-retardant antistatic composite modified polyester fiber and preparation method thereof

    CN118745608A

  • Fibrillated acrylic fibre

    CN1250493A

  • Noncombustible fabric and protective garment thereof

    CN201817647U

  • Flameproof modacrylic fibers

    US3824222A